The Authority of PPAT in Making APHT at PT. Bank Negara Indonesia - Wulan Pratiwi Yulia Djari; Salesius Jemaru; Baharudin Saleh Ingratubun (PT. Anagata Sembagi Education, 2025)
The Deed of Granting Dependent Rights (APHT) is a legal instrument that has a strategic role in ensuring certainty and legal protection for loans provided by banks. In practice, the making of APHT can only be done by the formally and territorially authorized Land Deed Making Officer (PPAT). This study aims to analyze the authority of PPAT in the manufacture of APHT at PT. Bank Negara Indonesia (Persero) Tbk, as well as identifying the implementation and legal obstacles that occur in practice. The research method used is an empirical juridical approach, with primary data collection through interviews with PPAT and credit officials at BNI Biak Branch Offices, as well as secondary data from laws and regulations and legal literature. The results of the study show that PPAT has exclusive authority in making APHT in accordance with Law Number 4 of 1996 concerning Dependent Rights. However, in the practice of cooperation with the bank, there are a number of challenges such as delays in submitting documents, lack of understanding of the debtor on legal procedures, and administrative obstacles in the process of registering dependent rights with the Land Office.